ANALISIS PENGARUH ONLINE CUSTOMER REVIEW, KUALITAS PRODUK DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA KONSUMEN SHOPEE MERCHANDISE K-POP (Studi Kasus Pada Pengguna Aplikasi Shopee Mahasiswa Fakulta - Kiswatus Salimah; Ika Wahyuni; Randika Fandiyanto (Fakultas Ekonomi dan Bisnis, 2025)
The growth of e-commerce and the rising popularity of Korean pop culture (K-pop) have driven increased consumption of merchandise through online platforms, particularly Shopee. This study aims to analyze the influence of online customer reviews, product quality, and product variety on purchase decisions, with purchase intention as an intervening variable. Employing a quantitative approach, the study targets students of the Faculty of Economics and Business at Abdurachman Saleh University, Situbondo. The sample was determined using simple random sampling and the Slovin formula, yielding 88 respondents. Data were collected through a questionnaire and analyzed using SmartPLS 3.0 software. The results indicate that online customer reviews and product quality have a positive, albeit statistically insignificant, influence on purchase intention, while product variety has a significant influence. All three independent variables have a significant impact on purchase decisions. However, purchase intention does not significantly affect purchase decisions and does not mediate the relationship between the independent variables and purchase decisions. These findings offer valuable insights for K-pop merchandise sellers on e-commerce platforms, informing the formulation of more effective marketing strategies.